2018
DOI: 10.15314/tsed.418840
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Linear Running and Change of Direction Performances of Male Soccer Players

Abstract: It is known that there is a strong correlation between agility performance and match performance in terms of soccer players. Moreover, it is expressed that the agility and the linear sprint have different performance skills. Therefore, the purpose of this study was to analyze the relationship between linear sprint and change of direction performance scores and to determine the most appropriate agility test for soccer players. 16 male soccer players (age: 21.93±3.62 years, height: 175.06±3.06 cm, body mass: 69.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Research has shown an explained variance of 61% to 79% between the 505 and IAT tests (r = 0.78 to 0.89, p < 0.01) [18], while Raya et al [19] showed an explained variance of 56% between the TT and the IAT (r = 0.75, p < 0.001). Furthermore, a study by Cinarli et al [20] on the TT showed an explained variance of 0% to 13% between the IAT, 505 test, and GewT test (−0.053–0.365; p = 0.164–0.846), and an explained variance of 26% between the 505 and IAT tests (r = 0.52; p = 0.041). These results are supported by Hachana et al [21], who also found an explained variance of 9% between the IAT and the 505 tests (r = 0.31; p = 0.002), and Draper and Lancaster [13], who show an explained variance of 6% between the IAT and the 505 tests (r = 0.25; p < 0.05).…”
Section: Introductionmentioning
confidence: 97%
“…Research has shown an explained variance of 61% to 79% between the 505 and IAT tests (r = 0.78 to 0.89, p < 0.01) [18], while Raya et al [19] showed an explained variance of 56% between the TT and the IAT (r = 0.75, p < 0.001). Furthermore, a study by Cinarli et al [20] on the TT showed an explained variance of 0% to 13% between the IAT, 505 test, and GewT test (−0.053–0.365; p = 0.164–0.846), and an explained variance of 26% between the 505 and IAT tests (r = 0.52; p = 0.041). These results are supported by Hachana et al [21], who also found an explained variance of 9% between the IAT and the 505 tests (r = 0.31; p = 0.002), and Draper and Lancaster [13], who show an explained variance of 6% between the IAT and the 505 tests (r = 0.25; p < 0.05).…”
Section: Introductionmentioning
confidence: 97%
“…For example, in male soccer players, a low correlation (r = 0.33) between 20-m straight sprint and 20-m zigzag tests has been reported [11] as well as in comparing 10-m straight sprint, flying 20-m, and 100° zigzag tests (r = 0.35 and r = 0.46, respectively) [12]. By contrast, moderate positive correlations were found between 10, 20, and 30 m sprint performances and the Illinois agility test, but not with the t-test [13]. In addition, Köklü et al [14] observed a moderate correlation (r = 0.56) between 10 m straight-sprint and 30 m straight-sprint performance, and a strong correlation between 10 m straight-sprint and zigzag tests composed of four 5-m sections set out at 100° angles (r = 0.74), whereas zigzag agility performance with the ball was not correlated with 20-m and 30-m sprint times in young soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that analyzed the relationship between different parameters and COD ability in men's soccer (Çinarli, Kafkas, & Kafkas, 2018;R. Hammami, Granacher, Pizzolato, Chaouachi, & Chtara, 2017;Loturco, Jeffreys, et al, 2020;Raya-González et al, 2020), while few authors investigated female soccer players (Kobal et al, 2021;Lockie, Dawes, & Jones, 2018;Pardos-Mainer et al, 2021) or other female athletes, such as volleyball, handball, basketball, and softball players (Banda, Beitzel, Kammerer, Salazar, & Lockie, 2019;Lockie, Dawes, & Callaghan, 2020;Nimphius, Mcguigan, & Newton, 2010;Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%